Approaches to Enhancing Social Innovation in Small Secondary School - Toonchaiyaphum, Matchuree; Sirisooksilp , Saowanee; Tuksino, Prakittiya (Dhammathas Academic Journal, 2022)
The objectives of this research were: 1) study the factors affecting social innovation in small secondary schools, 2) examine the consistency of A Structure Equation Model of Factors Affecting Social Innovation in Small Secondary Schools. Direct, indirect, and total influence, 3) study the approaches to enhancing Social Innovation in Small Secondary Schools. The research has been mixed method approach. Research methodology starting from Quantitative research 20 as much as the sample from the hypothetical model was used. Therefore, the sample was 240 small secondary schools. The informants for each school were administrators and teachers. A total of 480 respondents were included by multistage randomization. The instrument used was a questionnaire with Index of Consistency (IOC) is between 0.67-1.00 reliability value of 0.96 (Cronbach’s Alpha Coefficient), a semi-structured interview. And an in-depth interview Data were analyzed using the Mplus statistical program, descriptive statistics, and reference statistics. Followed by qualitative research using a sample of 3 small secondary schools with outstanding social innovations by selective selection. Key informants consisted of administrators, teachers, and school committees. Data were collected by studying school information and interviewing informants. Data collection tools are document study form Record form and in-depth interview form Analyze the data by content analysis. The results showed that: 1. The Confirmatory Factors of Social Innovation in Small Secondary Schools by the research showed a goodness-of-fit with statistical data as follows: x2 = 112.852, Df = 91, P-Value = 0.0601, RMSEA = 0.014, SRMR = 0.014, CFI = 0.999, TLI = 0.998. 2. Approaches to enhancing Social Innovation in Small Secondary Schools found that: Promotion of educational institutions to have concrete products that are innovative. Promote operations in accordance with the needs of society Use the school as a base to drive innovation to society. And promoting educational institutions to use community areas as a base to improve the quality of education of students. The results of the assessment of accuracy, suitability, feasibility, and usefulness. Overall, it’s at the highest level.